Country Partnership Framework for the Republic of Senegal for the Period FY20-FY24 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2020)
This five-year Country Partnership Framework (CPF) for Senegal lays out the World Bank Group (WBG) program for the FY20–FY24 period, which aims to support the country in its path towards achieving middle-income status by 2035.